Bioethics Cannot Afford to “Shut up and Dribble” - Ray, Keisha; Olmos Perez, Alexandra (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2026)
Bioethics’ sense of justice often manifests itself as what has become known as diversity, equity, and inclusion (DEI) values. As more DEI programs and initiatives are targeted, many bioethicists are being told some variation of “keep quiet about DEI and just do your job.” When bioethicists are told to abandon or “tone down” DEI a few things follow: 1) our job of challenging and questioning the morality of our collective and individual actions and encouraging others to do the same is ignored; 2) our professional identity and values are rewritten and weaponized against us; and 3) our socially situated identities outside our practice as bioethicists are disregarded; however, there is no bioethics without DEI work.